Targeting colorectal cancer cells using AND-gated adaptor RevCAR T-cells - Soto, Karla E. G.; Loureiro, Liliana R.; Bartsch, Tabea; Arndt, Claudia; Kegler, Alexandra; Mitwasi, Nicola; Drewitz, Laura; Hoffmann, Lydia; Saleh, Haidy A.; Crespo, Eugenia; Mehnert, Maria; Daglar, Cansu; et al. (Frontiers in Immunology, 2023)
Despite the success of chimeric antigen receptor (CAR) T-cells especially for treating hematological malignancies, critical drawbacks, such as "on-target, off-tumor" toxicities, need to be addressed to improve safety in translating to clinical application. This is especially true, when targeting tumor-associated antigens (TAAs) that are not exclusively expressed by solid tumors but also on healthy tissues. To improve the safety profile, we developed switchable adaptor CAR systems including the RevCAR system. RevCAR T-cells are activated by crosslinking of bifunctional adaptor molecules termed target modules (RevTM). In a further development, we established a Dual-RevCAR system for an AND-gated combinatorial targeting by splitting the stimulatory and co-stimulatory signals of the RevCAR T-cells on two individual CARs. Examples of common markers for colorectal cancer (CRC) are the carcinoembryonic antigen (CEA) and the epithelial cell adhesion molecule (EpCAM), while these antigens are also expressed by healthy cells. Here we describe four novel structurally different RevTMs for targeting of CEA and EpCAM. All anti-CEA and anti-EpCAM RevTMs 2 This is a provisional file, not the final typeset article were validated and the simultaneous targeting of CEA + and EpCAM + cancer cells redirected specific in vitro and in vivo killing by Dual-RevCAR T-cells. In summary, we describe the development of CEA and EpCAM specific adaptor RevTMs for monospecific and AND-gated targeting of CRC cells via the RevCAR platform as an improved approach to increase tumor specificity and safety of CAR T-cell therapies.